Secondary School Teachers and Learners Perspective for Future of Education Post COVID-19 Pandemic - El Rizaq, Agung Dwi Bahtiar; Sarmini, Sarmini (Universitas Islam Negeri Raden Intan Lampung, 2021)
The COVID-19 pandemic has become a global health disaster since March 2020 and has had a significant impact on education. The education system forced to change from a face-to-face learning model to a virtual one to reduce the spread of COVID-19. These extraordinary conditions that lasted no less than one year give various responses from both teachers and learners perspectives. This study examines secondary school teachers and learners perspectives regarding education in the future post, Covid-19 pandemic. This paper used the descriptive method by qualitative approach. Furthermore, this study was conducted by distributing online questionnaires from 5 provinces in Indonesia, involving 40 teachers and 28 learners. The results of this study indicate that (1) e-learning has not fully accommodated some educational values that can be transmitted through classical learning process only, (2) direct interaction are the most lost value during e-learning, (3) the sustainability of e-learning depends on the readiness of resources and infrastructure, and (4) blended learning is the suitable learning model for future education. From the result of these studies, identifying the suitable blended learning model for future education sustainability in every level of education is essential to be further studies as the stakeholder's reference in implementation learning models.